LAW ENFORCEMENT AGAINST THE CUSTOMARY RIGHTS OF INDIGENOUS PEOPLES OF PAPUA (STUDY OF SUPREME COURT DECISION NUMBER 1900/K/PDT/2024) - Finisia Bako; Abdul Razak Nasution (Yayasan Multidimensi Kreatif, 2025)
This study was conducted with the aim of determining the legal aspects of customary rights of indigenous peoples in the considerations of judges who decide on customary rights lawsuits in the Supreme Court decision number: 1900/K/Pdt/2024. This study uses normative juridical with a descriptive approach that aims to analyze carefully to solve problems in accordance with the applicable legal framework. In this study, the data sources used are secondary data in the form of Supreme Court case decisions number: 1900/K/Pdt/2024, laws and regulations and literature related to the research problems. Based on the results of the Supreme Court decision Number 1900/K/PDT/2024, it confirms the recognition of the customary rights of Papuan indigenous peoples as a form of collective ownership that is inherited from generation to generation. In this case, the customary land belonging to the Mandacan family is declared to remain theirs because it was never released through a legal mechanism according to customary law. However, land acquisition by other parties, including the issuance of Building Use Rights (HGB) certificates by the National Land Agency (BPN), was carried out without the consent or legal compensation to the customary owners. This action is considered an unlawful act because it does not respect the rights of indigenous peoples guaranteed by Article 18B of the 1945 Constitution. This decision also highlights the important role of state institutions, such as the BPN, in ensuring that land administration processes are carried out with respect for customary law and the rights of indigenous peoples.